Fluidizing agent special for arch ring wrapping C70 concrete as well as preparation method and application of fluidizing agent

By using composite flow agents of nano-silicon wafers, ultra-fine limestone powder, drift beads and ultra-fine talc powder, the problem that the fluidity and crack resistance of the arch ring outsourcing concrete are difficult to meet at the same time, and the comprehensive effect of high fluidity, large crack resistance and high late strength is achieved.

CN119797791APending Publication Date: 2025-04-11SOUTHEAST UNIV +2

Patent Information

Application Number
CN202510039090.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, the fluidity and crack resistance of the arch ring outsourcing concrete are difficult to meet at the same time, and high-strength concrete has problems such as poor workingability and large shrinkage and deformation during the construction process.

Method used

The composite flow agent of nano-silicon wafers, ultra-fine limestone powder, drift beads and ultra-fine talc powder is used to significantly improve the flowability of concrete through synergistic effects, and the later strength of concrete is improved without affecting crack resistance.

Benefits of technology

It significantly improves the flowability and crack resistance of concrete, reduces the difficulty of casting and vibration, ensures dense filling of concrete, and improves the later strength of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005236361330000061
    Figure BDA0005236361330000061
  • Figure BDA0005236361330000062
    Figure BDA0005236361330000062
Patent Text Reader

Abstract

The invention discloses a special fluidizing agent for covering C70 concrete outside an arch ring as well as a preparation method and application of the special fluidizing agent. The fluidizing agent is formed by compounding nano silicon wafers, superfine limestone powder, floating beads and superfine talcum powder, all the components have a synergistic effect, and the flowability of the concrete is improved through different mechanisms. The nanometer silicon wafer provides high specific surface area and active surface groups, lubrication among particles is promoted through electric coupling and ion excitation effects, internal friction resistance of the concrete is reduced, and the later strength of the concrete is improved through a volcanic ash reaction after hardening. The superfine limestone powder releases free water by destroying a flocculation structure, and plays a filling role. The floating beads serve as micron-sized spherical particles, and friction force among the particles is reduced. The superfine talcum powder has a sheet structure, and plays a role in dispersing and lubricating the cementing material. The fluidizing agent can be applied to large-flow-state and high-crack-resistance C70 concrete wrapped outside an arch ring, the problems that high-strength concrete is insufficient in fluidity and high in shrinkage cracking risk are effectively solved, and the construction performance and the engineering quality are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a fluidizing agent special for arch ring outer-wrapped concrete, a preparation method thereof, and application of the fluidizing agent in high-fluidity, high-cracking-resistance C70 concrete. Background Art

[0002] Steel tube concrete arch bridges have the advantages of high rigidity, high bearing capacity, low engineering cost and low later maintenance cost, so they have been widely used in mountainous and canyon terrains. my country has successfully built many large-span concrete arch bridges, making my country a world leader in the field of arch bridges. In response to the development of large-span concrete arch bridges in the new era, the strength, fluidity and crack resistance of the concrete wrapped around the arch ring have become key issues that need to be urgently addressed in the implementation of the project.

[0003] Among the existing steel tube concrete arch bridges, the grade of the main arch ring concrete material does not exceed C70. High-strength concrete of grade C70 and above has begun to be valued in projects such as long-span bridges due to its many performance advantages such as improving bearing capacity, reducing structural deadweight and saving materials. The prior art has improved some of the above problems by adjusting the mix ratio and adding admixtures and additives. For example, patent CN105272027B provides a method for preparing high-strength concrete. However, due to the low water-cement ratio and large amount of cementitious materials used, high-strength concrete generally has problems such as poor workability and large shrinkage deformation.

[0004] In addition, steel tube concrete arch bridges are mostly used in mountainous canyons, generally in environments with strong monsoons, alternating dry and wet air cycles, and uneven sunshine. The large-volume main arch ring has a large exposed area of ​​concrete, and the risk of concrete cracking is prominent. Patents CN114835422B and CN115745452B respectively provide a calcium-magnesium composite expansion clinker and a concrete anti-cracking material for reducing the shrinkage of concrete and improving the crack resistance of concrete. The addition of calcium-magnesium expansion clinker or anti-cracking material will reduce the fluidity of concrete, and the dynamic generation of reaction products will cause the loss of concrete fluidity to continue to increase.

[0005] How to take effective measures to reduce or even eliminate the fluidity loss caused by expansion clinker or anti-cracking materials, improve the fluidity of concrete, and ensure the dense filling of concrete is one of the urgent problems to be solved in arch ring outer wrapping concrete. It is urgent to develop a concrete for arch ring outer wrapping that has high strength, high fluidity and high crack resistance.

[0006] In summary, based on the theory of rheology and crack resistance of high-strength concrete, and from the perspectives of optimization of concrete raw materials, mix design, and application of key functional control materials, a preparation method for high-flow and high-crack-resistant concrete for arch ring wrapping can be proposed, aiming at the key requirements and potential technical methods for arch ring wrapping concrete. This method can improve the fluidity of concrete, reduce the difficulty of pouring and vibration, and achieve easy dense filling while controlling the risk of early shrinkage and cracking. It is of great significance to promote the high-quality development of large-span arch bridges and support the construction of a strong transportation country. Summary of the invention

[0007] The present invention proposes a special fluidizing agent for arch ring outer wrapping C70 concrete and a preparation method thereof, aiming to solve the problem that the concrete fluidity and crack resistance cannot be satisfied at the same time in the prior art. The fluidizing agent can continuously improve the fluidity of concrete and improve the strength of concrete in the later stage without affecting the crack resistance of concrete, and is particularly suitable for arch ring outer wrapping high-flow and high-crack resistance C70 concrete.

[0008] To achieve the above objectives, the specific technical solutions of the present invention are as follows:

[0009] An arch ring is wrapped with high-flow, high-crack-resistant C70 concrete, the components and dosage of which are: cement 380-430kg / m 3 、Fly ash 60~120kg / m 3 、Mineral powder 40~60kg / m 3 Silica fume 10~20kg / m 3 , sand 690~750kg / m 3 , Crushed stone 850~1100kg / m 3 、Flowing agent 15~30kg / m 3 , Anti-cracking agent 30~40kg / m 3 , Shrinkage reducing agent 5~10kg / m 3 , water reducing agent 5~10kg / m 3 , Water 150~165kg / m 3 .

[0010] In the above scheme, the cement is any one of P·O 52.5, P·I 52.5 or P·II 52.5 silicate cement; the fly ash is first-grade fly ash with a specific surface area greater than 400m 2 / kg, the activity index after 28 days is not less than 75%; the mineral powder is S95 mineral powder, the specific surface area is not less than 400m 2 / kg, the 28-day activity index is not less than 95%; the silicon dioxide content of the silica ash is not less than 85%, and the specific surface area is not less than 15000m 2 / kg.

[0011] In the above scheme, the sand is natural medium sand with a fineness modulus of 2.3 to 2.9, an apparent density of not less than 2630 kg / m3, and a mud content of less than 2%; the crushed stone is granite or basalt with a particle size of 5 to 16 mm and continuous grading, an apparent density greater than 2750 kg / m3, and the content of needle-shaped and flaky particles less than 2%.

[0012] In the above scheme, the fluidizing agent is a composite of nano silicon flakes, ultrafine limestone powder, floating beads and ultrafine talcum powder. The preferred components and mass ratios of the components are as follows:

[0013] 1) Nano silicon wafers: average particle size is 10-20 nanometers; mass percentage is 10-15%;

[0014] 2) Ultrafine limestone powder: average particle size is 2-5 microns; mass percentage is 30-40%;

[0015] 3) Floating beads: average particle size is 10-50 microns; mass percentage is 20-25%;

[0016] 4) Ultrafine talcum powder: average particle size is 6-8 microns; mass percentage is 20-25%.

[0017] The preparation method of the fluidizing agent comprises the following steps:

[0018] 1) According to the above ratio, weigh the nano silicon wafers, ultrafine limestone powder, floating beads and ultrafine talcum powder respectively;

[0019] 2) Place the weighed raw materials into a mixer and dry mix for 10-15 minutes to ensure that all components are evenly mixed;

[0020] 3) adding the dry-mixed mixture into an appropriate amount of deionized water to form a suspension, and stirring the suspension using a high shear mixer for 30 minutes at a speed of 2000 rpm to ensure that the nano-silicon wafers and other ultrafine powders are evenly dispersed in the water;

[0021] 4) heating the suspension to 60° C. and maintaining constant temperature stirring for 30 minutes to further improve the dispersibility and stability of each component;

[0022] 5) filtering the suspension after the heating treatment through a 100-mesh filter to remove possible undispersed particles, and cooling the filtered suspension to room temperature;

[0023] 6) Add 0.1-0.3% of the total amount of the suspension to the cooled suspension as a polycarboxylate water reducer as a stabilizer, stir evenly, and enhance the stability and dispersibility of the fluidizing agent;

[0024] 7) spray drying the stabilized suspension at a drying temperature of 150-180° C. to obtain a powder form of a fluidizing agent;

[0025] 8) The spray-dried powder is subjected to airflow milling for later use to ensure the fineness and uniformity of the fluidizing agent powder.

[0026] In the above scheme, the shrinkage reducing agent is a long side chain polyether modified polycarboxylic acid shrinkage reducing agent with a solid content of 20%; the water reducing agent is a polycarboxylic acid high-performance water reducing agent with a solid content of 20%; and the water is tap water.

[0027] The present invention also provides a method for preparing the arch ring outer-wrapped C70 concrete with high fluidity and high crack resistance, comprising the following steps:

[0028] 1) Weigh the raw materials of each component according to the mix ratio;

[0029] 2) Pour silicate cement, fly ash, mineral powder, silica fume, fluidizing agent and anti-cracking agent into a mixer and mix for 60 seconds to obtain solid powder;

[0030] 3) Add sand to the solid powder and stir for 30 seconds to obtain a mortar dry mix;

[0031] 4) adding the water reducing agent and the shrinkage reducing agent into water and mixing them evenly to obtain a diluted aqueous solution of the admixture;

[0032] 5) Add 3 / 4 of the diluted admixture aqueous solution to the mortar dry mix and stir for 120 seconds to obtain fresh mortar;

[0033] 6) Add crushed stone to the fresh mortar and stir for 60 seconds to obtain fresh concrete with normal flow state;

[0034] 7) Pour all the diluted admixture aqueous solution into the fresh concrete in the previous step and continue stirring for 120 seconds to obtain fresh concrete with high fluidity.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) Improve liquidity:

[0037] The fluidizing agent of the present invention significantly improves the fluidity of concrete through the synergistic effect of multiple components. Nano silicon chips can be adsorbed on the surface of cement particles due to their unique physical and chemical properties, and significantly reduce the friction resistance between cement particles through electrical coupling and ion excitation. Although the adsorption performance of ultrafine talcum powder is weak, its flaky structure is evenly dispersed in the system, effectively reducing the resistance inside the system. At the same time, the multi-angular structure of ultrafine limestone powder destroys the flocculation structure in the concrete, releases more free water, and improves workability. The floating beads are micron-sized spherical particles, which play a filling effect, reduce the friction between particles, and further enhance the fluidity of concrete. This makes it easier for concrete to fill complex mold structures during the pouring process, reducing the difficulty of pouring and vibrating.

[0038] (2) Control liquidity losses:

[0039] The design of the fluidizer takes into account the loss of fluidity caused by calcium-magnesium expansion clinker or anti-cracking materials during the reaction process. The synergistic effect of nano-silicon flakes and ultra-fine talcum powder with other components in the concrete system fully utilizes the advantages of their planar sheet structures, effectively alleviating the loss of fluidity caused by the dynamic generation of reaction products, and ensuring the stable fluidity of concrete during long-term construction.

[0040] (3) Enhanced crack resistance:

[0041] The added nano silicon flakes, ultrafine limestone powder, floating beads and ultrafine talcum powder not only play a filling and lubricating role, but also improve the density and crack resistance of concrete. In particular, the flaky structure of nano silicon flakes and ultrafine talcum powder effectively disperses evenly, reduces stress concentration, and further enhances the crack resistance.

[0042] (4) Improve the later strength of concrete:

[0043] The active silicon dioxide in the nano silicon wafer undergoes a volcanic ash reaction during the hardening process to generate more CSH gel, further improving the later strength of the concrete. By optimizing the composition and proportion of the fluidizing agent, the present invention ensures the early fluidity while also ensuring the high strength characteristics of the concrete after hardening.

[0044] (5) Wide applicability:

[0045] The fluidizing agent of the present invention is not only suitable for high-strength concrete of grade C70 and above, but also can be adjusted according to specific needs and applied to concrete of other strength grades. Its good fluidity, crack resistance and strength improvement effect make the present invention have a wide range of application prospects, can meet the requirements of high-performance concrete of different engineering projects, and has a wide range of application prospects.

[0046] In summary, the special fluidizing agent for arch ring outsourcing and its preparation method provided by the present invention, through scientific material selection and optimized preparation process, achieves the comprehensive effect of significantly improving the fluidity, crack resistance and later strength of concrete, meets the high requirements of modern high-strength concrete engineering for construction performance and durability, and provides reliable technical support for the construction of large-span bridges and other high-performance concrete structures. DETAILED DESCRIPTION

[0047] In order to further illustrate the content of the present invention, the technical scheme of the present invention is further described by the following specific examples. The following examples are only used to more clearly illustrate the technical scheme of the present invention, and cannot be used to limit the protection scope of the present invention.

[0048] The fluidizing agent of the present invention is composed of the following components by weight percentage: nano silicon chips (10-15%), ultrafine limestone powder (30-40%), floating beads (20-25%) and ultrafine talcum powder (20-25%). The nano silicon chips are prepared by chemical vapor deposition and have an average particle size of 10-20 nanometers; the ultrafine limestone powder has an average particle size of 2-5 microns; the floating beads have an average particle size of 10-50 microns; and the ultrafine talcum powder has an average particle size of 6-8 microns.

[0049] According to the above ratio, weigh the nano silicon wafers, ultrafine limestone powder, floating beads and ultrafine talcum powder respectively; put the weighed raw materials into the mixer, dry mix and stir for 10-15 minutes to ensure that the components are evenly mixed; take out the mixed dry powder, add an appropriate amount of deionized water to form a suspension, and use a high shear mixer to stir the suspension for 30 minutes at a speed of 2000 rpm to ensure that the nano silicon wafers and other powders are evenly dispersed in the water; heat the suspension to 60°C and keep constant temperature stirring for 30 minutes to further improve the dispersibility and Stability: filtering the heated suspension through a 100-mesh filter to remove possible undispersed particles, and cooling the filtered suspension to room temperature; adding 0.1-0.3% of the total amount of the suspension as a polycarboxylate water-reducing agent to the cooled suspension as a stabilizer, stirring evenly to enhance the stability and dispersibility of the fluidizing agent; spray drying the stabilized suspension at a drying temperature of 150-180° C. to obtain a powder form of the fluidizing agent; performing air flow milling on the spray-dried powder for standby use to ensure the fineness and uniformity of the fluidizing agent powder.

[0050] The prepared fluidizing agent is used to prepare concrete.

[0051] Example 1

[0052] The components and proportions are: cement 379kg / m 3 、Fly ash 77kg / m 3 、Mineral powder 41kg / m 3 、Silica fume 16kg / m 3 、Sand 702kg / m 3 、Crushed stone 1010kg / m 3 、Flowing agent 28kg / m 3 , anti-cracking agent 29kg / m3, shrinkage reducing agent 5.7kg / m 3 , water reducing agent 5.7kg / m 3 、Water 163kg / m 3 .

[0053] Among them, the fineness modulus of the sand is 2.9, the apparent density is 2630kg / m3, and the mud content is 1.3%; the crushed stone is diabase, with an apparent density of 2960kg / m3, a crushing value of 4.2%, and a needle-like content of 0.

[0054] Example 2

[0055] The components and proportions are: cement 397kg / m 3 、Fly ash 83kg / m 3 、Mineral powder 32kg / m 3 、Silica fume 19kg / m 3 、Sand 697kg / m 3 、Crushed stone 1046kg / m 3 、Flowing agent 28kg / m 3 , anti-cracking agent 29kg / m3, shrinkage reducing agent 5.7kg / m 3 , water reducing agent 5.7kg / m 3 , water 160kg / m 3 .

[0056] Among them, the fineness modulus of the sand is 2.9, the apparent density is 2630kg / m3, and the mud content is 1.3%; the crushed stone is diabase, with an apparent density of 2960kg / m3, a crushing value of 4.2%, and a needle-like content of 0.

[0057] Comparative Example 1

[0058] The same as Example 1, except that no fluidizing agent or anti-cracking agent is added, and the cementitious material is used to replace the fluidizing agent and anti-cracking agent in equal amounts according to the original proportion, and no shrinkage reducing agent is added, and the water reducing agent is used to replace the shrinkage reducing agent in equal amounts, that is, the concrete mix ratio is: cement 422kg / m 3 、Fly ash 85kg / m 3 、Mineral powder 45kg / m 3 、Silica fume 18kg / m 3 、Sand 702kg / m 3 、Crushed stone 1010kg / m 3 、Flowing agent 0kg / m 3 , anti-cracking agent 0kg / m3, shrinkage reducing agent 0kg / m 3 , water reducing agent 11.4kg / m 3 、Water 163kg / m 3 .

[0059] Comparative Example 2

[0060] The same as Example 1, except that no fluidizing agent is added, and the cementitious material is used to replace the fluidizing agent in the original proportion, that is, the concrete mix ratio is: cement 400kg / m 3 、Fly ash 81kg / m3 、Mineral powder 43kg / m 3 、Silica fume 17kg / m 3 、Sand 702kg / m 3 、Crushed stone 1010kg / m 3 、Flowing agent 0kg / m 3 , anti-cracking agent 29kg / m3, shrinkage reducing agent 5.7kg / m 3 , water reducing agent 5.7kg / m 3 、Water 163kg / m 3 .

[0061] Comparative Example 3

[0062] The same as Example 1, except that no anti-cracking agent is added, and the cementitious material is used to replace the anti-cracking agent in equal amounts according to the original proportion, and no shrinkage reducing agent is added, and the water reducing agent is used to replace the shrinkage reducing agent in equal amounts, that is, the concrete mix ratio is: cement 401kg / m 3 、Fly ash 81kg / m 3 、Mineral powder 43kg / m 3 、Silica fume 17kg / m 3 、Sand 702kg / m 3 、Crushed stone 1010kg / m 3 、Flowing agent 28kg / m 3 , anti-cracking agent 0kg / m3, shrinkage reducing agent 0kg / m 3 , water reducing agent 11.4kg / m 3 、Water 163kg / m 3 .

[0063] The contents of the various components of the concrete in the various embodiments and comparative examples are summarized in Table 1.

[0064] Table 1 Content of each component of concrete in each embodiment and comparative example

[0065]

[0066] The concrete of the above-mentioned embodiments and comparative examples are prepared according to the following steps: weighing the raw materials of each component according to the mix ratio; adding cement, fly ash, mineral powder, silica fume, fluidizing agent and anti-cracking agent to a mixer in sequence and mixing for 60 seconds to obtain a solid powder; adding sand to the solid powder and mixing for 30 seconds to obtain a mortar dry mix; adding a water reducer and a shrinkage reducer to water and mixing evenly to obtain an admixture diluted aqueous solution; adding 3 / 4 of the admixture diluted aqueous solution to the mortar dry mix and stirring for 120 seconds to obtain a fresh mortar; adding crushed stone to the fresh mortar and stirring for 60 seconds to obtain a fresh concrete with a general flow state; pouring all the admixture diluted aqueous solution into the fresh concrete in the previous step and continuing to stir for 120 seconds to obtain a fresh concrete with a large flow state.

[0067] The concrete prepared in the embodiment and the comparative example was tested for workability, mechanical properties and crack resistance. The workability of the concrete was evaluated by the concrete expansion and t500 time, the workability loss of the concrete was evaluated by comparing the workability change after 30 minutes, the mechanical properties of the concrete were evaluated by the 7d and 28d compressive strength, and the crack resistance of the concrete was evaluated by the 28d shrinkage rate. The measured results are summarized in Table 2.

[0068] Table 2 Working performance and mechanical properties of concrete in various embodiments and comparative examples

[0069]

[0070] Note: A negative shrinkage value indicates that the specimen shrinks, and a positive shrinkage value indicates that the specimen expands.

[0071] It can be seen from the experimental results that the C70 concrete prepared by the present invention has the performance characteristics of high crack resistance, large flow state and low flow loss while meeting the strength requirements, and the workability of the concrete is almost unchanged after half an hour.

[0072] Comparative Example 1 does not contain a fluidizing agent, an anti-cracking agent, and a shrinkage reducing agent, and the other components are the same as those in Example 1. The measurement results show that the lack of a fluidizing agent, an anti-cracking agent, and a shrinkage reducing agent simultaneously leads to a decrease in the fluidity of the concrete, an increase in viscosity, a large loss in the fluidity of the concrete, a large shrinkage of the concrete, and poor anti-cracking performance. In addition, the compressive strength of the concrete is slightly reduced.

[0073] In Comparative Example 2, no fluidizing agent was added, and the other components were the same as those in Example 1. The measurement results showed that the lack of fluidizing agent would significantly reduce the fluidity of the concrete, increase the viscosity of the concrete, and cause a significant loss of fluidity of the concrete after 30 minutes. In addition, the compressive strength of the concrete was slightly reduced. However, due to the addition of anti-cracking agent and shrinkage reducing agent, the anti-cracking performance of the concrete was good.

[0074] Comparative Example 3 was not mixed with anti-cracking agent and shrinkage reducing agent, and the other components were the same as Example 1. The measurement results showed that due to the addition of the fluidizing agent, the fluidity of the concrete was good, showing the characteristics of a large flow state, and the fluidity of the concrete was not lost after 30 minutes. The lack of anti-cracking agent and shrinkage reducing agent will cause plastic shrinkage of concrete, and the crack resistance is poor. However, nano silicon flakes and ultrafine talcum powder in the fluidizing agent reduce stress concentration, improve crack resistance to a certain extent, and the shrinkage degree is reduced compared to Comparative Example 1. In addition, due to the small particle size of the fluidizing agent, the pores inside the concrete are filled, the density of the concrete is improved, and the compressive strength of the concrete is improved.

[0075] The above are only some of the disclosed embodiments of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and adjustments can be made without departing from the technical principles of the present invention. These improvements and adjustments should also be regarded as within the scope of protection of the present invention.

Claims

1. A fluidizing agent specially used for C70 concrete for arch ring outer covering, characterized by: The invention is composed of the following components by mass percentage: 10-15% of nano silicon wafers, 30-40% of ultrafine limestone powder, 20-25% of floating beads and 20-25% of ultrafine talcum powder.

2. The fluidizing agent according to claim 1, characterized in that: The average particle size of nano silicon wafers is 10-20 nanometers; the average particle size of ultrafine limestone powder is 2-5 microns; the average particle size of floating beads is 10-50 microns; and the average particle size of ultrafine talcum powder is 6-8 microns.

3. The method for preparing the fluidizing agent according to claim 1, characterized in that: The following steps are involved: Step S1: weighing nano silicon wafers, ultrafine limestone powder, floating beads and ultrafine talcum powder respectively according to mass percentage; Step S2: dry mixing, wet mixing and heating mixing are sequentially performed on the weighed components to obtain a suspension; Step S3: filtering the suspension and cooling it to room temperature; Step S4: adding a stabilizer to the cooled suspension and stirring the mixture to enhance the stability and dispersibility of the fluidizing agent; Step S5: drying the stabilized suspension to obtain a powder form of a fluidizing agent; Step S6: The dried powder is subjected to air flow milling for standby use to ensure the fineness and uniformity of the fluidizing agent powder.

4. The preparation method according to claim 3, characterized in that: Step S2 specifically includes: Step S2.1: Place the weighed raw materials into a mixer and dry mix for 10-15 minutes to ensure that the components are evenly mixed; Step S2.2: adding the dry-mixed mixture into an appropriate amount of deionized water to form a suspension, and stirring the suspension using a high shear mixer for 30 minutes at a speed of 2000 rpm to ensure that the nano-silicon wafers and other ultrafine powders are evenly dispersed in the water; Step S2.3: The suspension is heated to 60°C and stirred at a constant temperature for 30 minutes to further improve the dispersibility and stability of each component.

5. The preparation method according to claim 3, characterized in that: The stabilizer is a polycarboxylate water reducer, and its mass accounts for 0.1-0.3% of the total amount of the suspension.

6. The preparation method according to claim 3, characterized in that: The drying process in step S5 is spray drying, and the drying temperature is 150-180°C.

7. The use of the fluidizing agent according to claim 1, characterized in that: When used for preparing C70 concrete with high fluidity and crack resistance for arch ring wrapping, the fluidizing agent is added to the concrete raw materials of cement, fly ash, mineral powder, silica fume, sand, crushed stone, anti-cracking agent, shrinkage reducing agent, water reducing agent and water and mixed thoroughly.

8. The use of the fluidizing agent according to claim 7, characterized in that: The components and dosage of the concrete are as follows: cement 380-430kg / m 3 、Fly ash 60-120kg / m 3 、Mineral powder 40-60kg / m 3 、Silica fume 10-20kg / m 3 , sand 690-750kg / m 3 , Crushed stone 750-900kg / m 3 、Flowing agent 15-30kg / m 3 , Anti-cracking agent 30-40kg / m 3 , Shrinkage reducing agent 5-10kg / m 3 , water reducing agent 5-10kg / m 3 , Water 150-165kg / m 3 .

9. The use of the fluidizing agent according to claim 7, characterized in that: The cement is any one of P·O 52.5, P·I 52.5 or P·II 52.5 silicate cement; the fly ash is first-grade fly ash with a specific surface area greater than 400m 2 / kg, the activity index after 28 days is not less than 75%; the mineral powder is S95 mineral powder, the specific surface area is not less than 400m 2 / kg, the 28-day activity index is not less than 95%; the silica content of the silica ash is not less than 85%, and the specific surface area is not less than 15000m 2 / kg; the sand is natural medium sand, with a fineness modulus of 2.3 to 2.9 and an apparent density of not less than 2630 kg / m 3 The mud content is less than 2%; the crushed stone is granite or basalt, with a particle size of 5 to 16 mm and continuous grading, and an apparent density greater than 2750 kg / m 3 , the content of needle and flake particles is less than 2%.

10. A method for preparing an arch ring with high-flowability and high-crack-resistance C70 concrete, characterized in that: The steps include: Step S1: weighing the raw materials of each component according to the composition and dosage in claim 8; Step S2: pouring silicate cement, fly ash, mineral powder, silica fume, fluidizing agent and anti-cracking agent into a mixer and mixing for 60 seconds to obtain a solid powder; Step S3: adding sand to the solid powder and stirring to obtain a mortar dry mix; Step S4: adding the water reducing agent and the shrinkage reducing agent into water and mixing them evenly to obtain a diluted aqueous solution of the admixture; Step S5: adding part of the diluted aqueous solution of the admixture to the mortar dry mix and stirring to obtain a freshly mixed mortar; Step S6: adding crushed stone to fresh mortar and mixing to obtain fresh concrete in a normal fluid state; Step S7: pour the remaining part of the diluted admixture aqueous solution into the fresh concrete in the previous step and continue stirring to obtain fresh concrete with high fluidity.

Citation Information

Patent Citations

  • Ultra-high performance concrete with compressive strength above 300 MPa and its preparation method

    CN105272027B

  • A calcium-magnesium composite expandable clinker, its preparation method, and its application in low-shrinkage, high-crack-resistant marine mass concrete.

    CN114835422B

  • Concrete anti-cracking material, preparation method and application thereof

    CN115745452B

Cited By

  • Truck scale based on UHPC high-performance lightweight concrete material and preparation method thereof

    CN121377672A

  • A truck scale based on UHPC high-performance lightweight concrete material and a preparation method thereof

    CN121377672B